IMPRONTAS FOLIARES DE UNA LAURACEAE EN LA FORMACIÓN PARANÁ (MIOCENO SUPERIOR), EN VILLA URQUIZA, ENTRE RÍOS (Ameghiniana, 2014)
Leaves of Ocotea sp. (Lauraceae), are identified and described. They were found in argilIaceous beds of Paraná Formation in Villa Urquiza, Entre Rios Province, Argentina. The affinities and palaeobiogeographical relations are discussed.